E-WOM, Customer Review, dan Perceived Value terhadap Purchase Decision Produk Glad2Glow - Suketyi, Ayu Tri Lestari; Fidhyallah, Nadya Fadillah; Rizka Zakiyah (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
This study aims to examine the influence of electronic word of mouth (e-WOM) and customer reviews on the purchase decision of Glad2Glow products in DKI Jakarta, with perceived value as an intervening variable. Using a quantitative approach, data were collected through an online survey of 217 respondents and analyzed using Structural Equation Modeling (SEM) via SPSS and Amos. The results indicate that e-WOM has a positive and significant effect on both perceived value and purchase decision, and its effect is significantly mediated by perceived value. Meanwhile, customer reviews also have a significant positive effect on perceived value and purchase decision, but their effect is not mediated by perceived value. These findings suggest that customer reviews have a more direct influence on purchase decisions. This study contributes theoretically to digital consumer behavior research and offers practical implications for skincare product digital marketing strategies. Keywords: e-WOM, customer review, perceived value, purchase decision.